2006
DOI: 10.1016/j.neuron.2006.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A Preformed Complex of Postsynaptic Proteins Is Involved in Excitatory Synapse Development

Abstract: Nonsynaptic clusters of postsynaptic proteins have been documented; however, their role remains elusive. We monitored the trafficking of several candidate proteins implicated in synaptogenesis, when nonsynaptic clusters of scaffold proteins are most abundant. We find a protein complex consisting of two populations that differ in their content, mobility, and involvement in synapse formation. One subpopulation is mobile and relies on actin transport for delivery to nascent and existing synapses. These mobile clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
192
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(221 citation statements)
references
References 48 publications
23
192
3
1
Order By: Relevance
“…Together, these findings suggest that increased alterations of PSD form are part of a rapid remodeling process synapses undergo during accommodation to changes in network activity. It will be important to learn how control of PSD-95 scaffold dynamics relates to the reported regulation of PSD-95 protein accumulation, dispersal, and degradation at synapses (13,21,23,24,(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these findings suggest that increased alterations of PSD form are part of a rapid remodeling process synapses undergo during accommodation to changes in network activity. It will be important to learn how control of PSD-95 scaffold dynamics relates to the reported regulation of PSD-95 protein accumulation, dispersal, and degradation at synapses (13,21,23,24,(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…Recent live-imaging experiments have focused on the accumulation and dispersal of PSD scaffolds during synaptogenesis or synapse loss (19)(20)(21)(22), the translocation of assembled PSD scaffolds in developing neurons as synapses form (23), or the rates of exchange of various PSD constituents (22,(24)(25)(26). However, the submicron size of the PSD has hindered analysis of its morphology and internal architecture in living neurons.…”
mentioning
confidence: 99%
“…Flux in the density of excitatory postsynaptic scaffold clusters over time along dendritic segments has also been reported, with an interesting synchronization within a given cell (Ebihara et al, 2003). Although merging of clusters has been observed (Gerrow et al, 2006), a major mode for reduction of excitatory postsynaptic scaffold clusters is by elimination or disappearance without obvious merging (Okabe et al, 1999;Niell et al, 2004). For inhibitory postsynaptic scaffold clusters, our observations suggest that merging may be a major mode for reducing the number of synaptic clusters while concomitantly increasing individual synapse size due to the merge (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…New PSD-95 clusters formed mainly in dendrite protrusions by gradual accumulation from cytosolic pools, with a slight delay following the appearance of apposed synaptic vesicle clusters (Bresler et al, 2001;Okabe et al, 2001a). However, mobile clusters of postsynaptic scaffolds and stationary postsynaptic clusters that can recruit presynaptic vesicles have also been observed (Gerrow et al, 2006). Stable postsynaptic scaffold clusters were associated with stabilization of dendritic protrusions (Prange and Murphy, 2001) and developed along newly grown dendrite branches over several days (Ebihara et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…CaMKII expression is important for synapse formation and maturation [8][9][10][11][12], and previous work from our laboratory demonstrated that overexpression of constitutively active CaMKII enhances connectivity between active presynaptic partners by increasing new contact formation [13,14]. The scaffold protein PSD-95 is highly abundant at [15], and clusters very early at [16][17][18] excitatory synapses. Further, PSD-95 is more strongly associated with stable than transient spines [19], and is thought to accelerate synaptic maturation [3,[20][21][22] through coordinated regulation of postsynaptic AMPA-type glutamate receptors (GluARs) [23][24][25] and neuroligins [26,27].…”
Section: Introductionmentioning
confidence: 78%